Cost-Analysis-Based Strategy for Load Balancing in Multi-Induction Motor Systems - Nayak, Roopa; Pallavi, Andhe (Engineering Research: Perspectives on Recent Advances Vol. 4, 2025)
A major concern for any industrial process, military, naval, aerospace, and satellite application, at various stages of process is the reliability. A stall in the process at any stage of production in an industrial process would result in a product with low quality. The majority of the industrial processes are generally carried out using a motor-drive arrangement. The quality of the final output of a process largely depends on the performance and reliability of the motor drive sets. Failure of motor running the process can result in a complete shutdown of the process. Certain processes may not even afford to offer downtime for maintenance. Downtime of motors can severely affect the quality of the endproduct of a process. The performance parameters employed for the cost analysis of motors are obtained from the manufacturer. It was found that although there are many tools and algorithms to predict the failure and maintenance patterns for motor, this paper presents a novel means to increase the reliability of motor-drive arrangements. It also presents a cost analysis framework for choosing a motor-drive arrangement for a particular load. In conclusion, an algorithm is developed to find the optimum number of RIMs. Two case studies are presented to show how the developed algorithm can be applied to calculate the optimum number of RIM.